Deterministic realization of collective measurements via photonic quantum walks - Zhibo Hou (Nature Portfolio, 2018)
Demonstrating the advantage of collective measurements in experiments remains a daunting task. Here the authors introduce a general recipe for performing deterministic collective measurements on two identically prepared qubits based on quantum walks.